2017
DOI: 10.1215/03616878-3940468
|View full text |Cite
|
Sign up to set email alerts
|

People, Places, Power: Medicaid Concentration and Local Political Participation

Abstract: The geographic concentration of disadvantage is a key mechanism of inequity. In the United States, the spatial patterning of disadvantage renders it more than the sum of its individual parts and disproportionately harms economically and racially marginalized Americans. This article focuses specifically on the political effects of Medicaid beneficiaries being concentrated in particular locales. After offering a framework for conceptualizing the community-wide consequences of such policy concentration, I analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 77 publications
1
40
0
Order By: Relevance
“…Social scientists have interrogated a wide spectrum of policy domains with an eye toward race. They have studied welfare, health, education, labor markets, criminal justice, voting rights, and much more (Brown, 1999;Bruch & Soss, 2018;Cohen, 1999;Harris & Lieberman, 2013;Hero & Tolbert, 1996;Katznelson, 2005Katznelson, , 2013Matsubayashi & Rocha, 2012;Michener, 2016;Mink, 1990;Murakawa, 2014;Pager, 2007;Soss et al, 2011;Soss & Weaver, 2017;Tolbert & Hero, 2001;Weaver, 2007;Western, 2006;Williams, 2003). Time and again, such research has confirmed that race is (and has long been) a fundamental factor in explaining policy development, implementation, outputs, and outcomes.…”
Section: Race and American Public Policymentioning
confidence: 99%
See 4 more Smart Citations
“…Social scientists have interrogated a wide spectrum of policy domains with an eye toward race. They have studied welfare, health, education, labor markets, criminal justice, voting rights, and much more (Brown, 1999;Bruch & Soss, 2018;Cohen, 1999;Harris & Lieberman, 2013;Hero & Tolbert, 1996;Katznelson, 2005Katznelson, , 2013Matsubayashi & Rocha, 2012;Michener, 2016;Mink, 1990;Murakawa, 2014;Pager, 2007;Soss et al, 2011;Soss & Weaver, 2017;Tolbert & Hero, 2001;Weaver, 2007;Western, 2006;Williams, 2003). Time and again, such research has confirmed that race is (and has long been) a fundamental factor in explaining policy development, implementation, outputs, and outcomes.…”
Section: Race and American Public Policymentioning
confidence: 99%
“…A substantial and growing body of research has shown that the structure and design of government programs (and the organizations to which they delegate) can influence political decision making across a broad spectrum of actors by channeling resources, generating interests, and shaping interpretive schemas (Barnes, 2018;Béland, 2010;Campbell, 2003Campbell, , 2012Goss, 2013;Mettler & SoRelle, 2014;Mettler & Soss, 2004;Michener, 2018;Morgan & Campbell, 2011;Pierson, 1993;Schneider & Ingram, 1993;Skocpol, 1992;Soss, 2000). In the United States, each of these mechanisms implies a role for race.…”
Section: Race and Policy Feedbackmentioning
confidence: 99%
See 3 more Smart Citations